Body mass index and cognitive function: Birth cohort effects in young men. (10th April 2015) - Ehrenstein, Vera; Münster, Anna‐Marie Bloch; Milstein, Arnold; Adler, Nancy E.; Sørensen, Henrik Toft
<x xml:space="preserve">Abstract</x> Objective Body mass index (BMI) and intelligence quotient (IQ) are associated. We examined whether this association varied by birth cohort. Methods Among 37, 414 Danish conscripts, the association between BMI and IQ overall and by birth cohort was examined. IQ was measured by the Børge Prien's Prøve (BPP) group intelligence test score. Results Compared with men of normal BMI, mean differences (95% CI [confidence interval]) in BPP score were −0.6 (−1.1;–0.1) for underweight men; −0.8 (−1.1;–0.5) for overweight men; and −2.0 (−2.4;–1.5) for men with obesity. Crude prevalence ratios (95% CI) for low cognitive scores associated with obesity were, respectively, 1.52 (1.24; 1.85), 1.64 (1.32; 2.04), 1.56 (1.38; 1.76), and 1.35 (1.18; 1.54) among men born in 1955, 1965–1969, 1970–1979, and 1980–1984. Confounding by familial BMI or IQ could not be controlled. Conclusions The association between BMI and IQ is subject to secular trends.